A Theoretical Investigation of ZnO Nanotubes: Size and Diameter - de Moraes, Eduardo; Gargano, Ricardo; R. dos Santos Politi, José; A. S. de Castro, Elton; Divino dos Santos, Jose; Longo, Elson; A. Taft, C.; B. L. Martins, Joao (Current Physical Chemistry, 2013)
We have studied zinc oxide single-walled nanotubes and the effects of increasing the diameter of the nanotube and the size along its c-axis. The armchair and zigzag structures were calculated using the semiempirical AM1 and ab initio RHF/3-21G method. The Zn-O distance was optimized in order to search for the stable structure minimum energy. The structure of minimum energy for the dZn-O distance is used for the analysis of energy variation, gap (HOMO-LUMO) and charge values. Our results show that increasing the nanotube size the Zn-O distance tends to 1.96Å and 2.0Å for the armchair and zigzag nanotubes near the experimental bulk value, respectively.
Keywords: semiempirical